Legal Analysis of Government Intervention in the Management of Cassava Agricultural Commodities in East Lampung Regency - Pribadi, Adhimaz Kondang; Gautama, Tirta (Research Horizon, 2025)
This article aims to analyze the government's legal intervention in the management of cassava as an agricultural commodity in East Lampung Regency through a normative juridical approach. The background of this study stems from the weak bargaining position of farmers in the cassava value chain and the lack of effective legal protection at the regional level. This research applies normative legal methods by examining statutory regulations, legal doctrines, and relevant academic literature. The findings indicate that although the legal basis for state intervention is sufficiently established at the national level, its implementation remains ineffective due to the absence of clear operational norms, disharmony between central and regional regulations, and the lack of legal enforcement mechanisms to control exploitative market practices. The implications highlight the urgent need for a regional regulation that specifically governs cassava trade systems, including price floor policies, legal empowerment of farmer cooperatives, and strengthened legal oversight through administrative law instruments. A law-based government intervention is necessary to ensure economic justice distribution and meaningful protection for vulnerable groups in the agricultural sector.